New urbanization, income gap between urban and rural areas and economic growth-empirical analysis based on the Yangtze River Delta region - Wu Jiaxin (E3S Web of Conferences, 2022)
Under the current background of common prosperity, studying the dynamic relationship between the new urbanization, urban-rural income gap and economic growth in the Yangtze River Delta is conducive to the coordinated and integrated development of our country. Based on the relevant data of the Yangtze River Delta from 2001 to 2020, the VECM model is used for impulse response and variance decomposition analysis. The results show that economic growth significantly affects the development of new urbanization; The impact of new urbanization and economic growth on urban-rural income gap is heterogeneous; Both have a positive impact on economic growth, but the new urbanization has a stronger role in promoting economic growth.